Muslims in Spain, 1500 to 1614 - Harvey, L. P. (Leonard Patrick) (University of Chicago Press, 2005)
On December 18, 1499, the Muslims in Granada revolted against the Christian city government's attempts to suppress their rights to live and worship as followers of Islam. Although the Granada riot was a local phenomenon that was soon contained, subsequent widespread rebellion provided the Christian government with an excuse?or justification, as its leaders saw things?to embark on the systematic elimination of the Islamic presence from Spain, as well as from the Iberian Peninsula as a whole, over the next hundred years. Picking up at the end of his earlier classic study, Islamic Spain, 1250 to.